Sensing Siberia - Art Leete (Journal of Ethnology and Folkloristics)
Report of the 10th Siberian Studies Conference titled Passion for Life: Emotions, Feelings, and Perception in the North and Siberia held in Saint Petersburg, October 24–26, 2016.